Propuesta de privatización del BCR: Mitos y realidades sobre la banca pública y la banca privada en Costa Rica (Revista Rupturas, 2023)
The privatization proposal of the Bank of Costa Rica (BCR), has made necessary to revisit the old controversy about the role and contributions of public banks in Costa Rica, relative to those offered by private banks, in the last months of 2022. In particular, President Chaves himself fueled the controversy by justifying his proposal, ensuring that private banking is more efficient than public banking, and that a private BCR would give better contributions than it delivers by being public. On the other hand, such statements reiterate a commonplace, solidly installed in the dominant neoliberal discourse in Costa Rica. These statements by President Chaves inspired this work, to try to answer a very basic question: is private banking really more efficient and bears fruit of greater social benefit than public banking? This article proves that to be false.
Keywords: Economy; Bank; Social Science